Strategic Considerations To New Product Development(NPD) And Product Launch In Pakistan - Arif, Salman (2013)
The aim of the research was to understand what problems and considerations companies needed to take into account when launching new products in emerging markets, particularly by looking at the case of Pakistan. For this purpose semi-structured, in-depth interview approach was used with nine marketing professionals from renowned multinational corporations and local firms based in Karachi, Pakistan. Based on these interviews, the author derived four main themes which address the research question.